Persepsi Pembudidaya Ikan Terhadap Kompetensi Penyuluh Perikanan di Kawasan Minapolitan (Kasus di Kabupaten Cirebon, Provinsi Jawa Barat) - Haryadi, Ikhsan; Amanah, Siti; Suriatna, Suwardi (Jurnal Penyuluhan, 2015)
Research objectives were: 1) to describe the profile fish farmers, 2 ) to analyze the perception of fish farmers towards competence of fisheries extension worker, and 3 ) to analyze the relationship between the profile of fish farmers and fisheries extension services towards of fish farmers perceptions of competence of fisheries extension workers. The study was conducted in Cirebon regency, West Java Province. The sample was 100 respondents of fish farmers is determined by the formula Slovin. Processing and analysis of data using descriptive statistics and inferential statistics (Rank Spearmen). The results showed profiles of fish farmers mostly adult age category (39-57 years). Majority of low educational level or not complete primary school or complete primary school. Participation in fisheries training and experience of fishing bussines is low. Perceptions of fish farmer towards competence of fisheries extension worker is the medium category, except towards personal competence is high category with details of the personal competence is 64%, andragogik competence is 61%, professional competence is 59% and social competence is 60% The better the extension given material, the better the fisheries extension perceptions fish farmers to professional and social competence fisheries extension workers. The better implementation methods and techniques of extension, the better the perception of fish farmers towards personal competence, social and professional of fisheries extension workers.Keywords: fish farmers’s perception, competence of fisheries extension worker, minapolitan region